2014
DOI: 10.1007/s00705-014-2105-4
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome-localized hepatitis Bx protein increases the invasion property of hepatocellular carcinoma cells

Abstract: HBx acts as a multifunctional regulator that modulates various cellular responses, which can lead to development and progression of hepatocellular carcinoma (HCC). Here, we show that the HBx protein is also localized to peroxisomes, and this increases cellular reactive oxygen species (ROS) to levels that are higher than when HBx is localized to other organelles. The elevated ROS strongly activated nuclear factor (NF)-κB. In addition, the peroxisome-localized HBx increased the expressions of matrix metalloprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Since our findings show that the TP domain contains the MTS, it still remains to be seen if localization of Pol to the mitochondria plays a role in the reported interaction between Pol and STING (73). HBx, a regulatory protein specific to mammalian hepadnaviruses, has also been detected at mitochondria in some studies (75)(76)(77)(78). HBx has been linked to both pro-and antiapoptotic roles, mitochondrial membrane potential modulation, generation of oxidative stress, and downregulation of innate immune responses (79).…”
Section: Discussionmentioning
confidence: 69%
“…Since our findings show that the TP domain contains the MTS, it still remains to be seen if localization of Pol to the mitochondria plays a role in the reported interaction between Pol and STING (73). HBx, a regulatory protein specific to mammalian hepadnaviruses, has also been detected at mitochondria in some studies (75)(76)(77)(78). HBx has been linked to both pro-and antiapoptotic roles, mitochondrial membrane potential modulation, generation of oxidative stress, and downregulation of innate immune responses (79).…”
Section: Discussionmentioning
confidence: 69%
“…In addition, it has been shown that (i) several RNA viruses that are of great importance for global public health (e.g., rotavirus, HIV, and influenza) exploit these organelles in their replication cycle [176,177,178]; (ii) pathogenic flaviviruses such as West Nile and dengue impair peroxisome biogenesis in infected cells, thereby suppressing the induction of type III IFNs [179]; and (iii) hepatitis B virus X protein, a multifunctional viral protein that binds to MAVS and promotes the development and progression of hepatocellular carcinoma, triggers the production of ROS and activation of NF-κB upon association with mitochondria [180] or peroxisomes [181]. In summary, these observations highlight the critical and cooperative role of peroxisomes and mitochondria in antiviral defense.…”
Section: Peroxisome-mitochondria Communication: Physiological Impomentioning
confidence: 99%
“…However, a limited but growing number of studies lend strong support to the idea that these organelles do actively contribute to transcompartmental ROS signaling in mammalian cells (Figure 2 ). For example, alterations in peroxisomal H 2 O 2 metabolism have been shown to influence the cellular protein disulfide content (Yang et al, 2007 ; Ivashchenko et al, 2011 ), NF-kB activation (Li et al, 2000 ; Han et al, 2014 ), E-cadherin expression (Han et al, 2014 ), the secretion of matrix metalloproteinases (Koepke et al, 2008 ; Han et al, 2014 ), mTORC1 activity and autophagy (Zhang et al, 2013 ), neuronal activity (Diano et al, 2011 ), and cell fate decisions in response to different stressors (Carter et al, 2004 ; Chen et al, 2004 ; Elsner et al, 2011 ). Unfortunately, the precise molecular mechanisms underlying most of these observations remain poorly understood and sometimes even controversial.…”
Section: Peroxisomes As Redox Signaling Nodesmentioning
confidence: 99%